Introduction of 18 F FDG PET-CT Imaging of Inflammatory Diseases at NINMAS - Begum, Shamim MF (Bangladesh Journal of Nuclear Medicine, 2018)
Abstract not available Bangladesh J. Nuclear Med. 20(2): 97-98, July 2017